Анализ физических факторов, формирующих отраженный звуковой сигнал в АПС - Слипченко, Н. И.; Лю, Чан; Панченко, А. Ю. (ХНУРЭ, 2011)
The modern state of systems and methods for the atmosphere acoustic sounding is analyzed. Physical factors forming the reflected acoustic signal are generalized. The problems, which are the most urgent at present, are formed. Possible ways of performing the sounding methods and systems are considered.
Keywords: экологические проблемы; контроль природной среды